Metabolic and Stress Response Changes Precede Disease Onset in the Spinal Cord of Mutant SOD1 ALS Mice - Pharaoh, Gavin; Sataranatarajan, Kavithalakshmi; Street, Kaitlyn; Hill, Shauna; Gregston, Jake; Ahn, Bumsoo; Kinter, Caroline; Kinter, Michael; Van Remmen, Holly (Frontiers in Neuroscience, 2019)
Many Amyotrophic Lateral Sclerosis (ALS) patients experience hypermetabolism, or an increase in measured versus calculated metabolic rate. The cause of hypermetabolism and the effects on neuronal metabolism in ALS are currently unknown, but the efficacy of dietary interventions shows promise for metabolism as an ALS therapeutic target. The goal of this study is to measure changes in metabolic pathways as a function of disease progression in spinal cords of the SOD1G93A mouse model of ALS. We conducted a comprehensive assessment of protein expression for metabolic pathways, antioxidants, chaperones, and proteases in lumbar spinal cord from male SOD1G93A mice at pre-onset, onset, and end-stages of the disease using targeted proteomic analysis. These results reveal that protein content of metabolic proteins including proteins involved in glycolysis, β-oxidation, and mitochondrial metabolism is altered in SOD1G93A mouse spinal cord well before disease onset. The changes in mitochondrial metabolism proteins are associated with decreased maximal respiration and glycolytic flux in SOD1G93A dermal fibroblasts and increased hydrogen peroxide and lipid hydroperoxide production in mitochondria from sciatic nerve and gastrocnemius muscle fibers at end stage of disease. Consistent with redox dysregulation, expression of the glutathione antioxidant system is decreased, and peroxiredoxins and catalase expression are increased. In addition, stress response proteases and chaperones, including those involved in the mitochondrial unfolded protein response, are induced before disease onset. In summary, we report that metabolic and stress response changes occur in SOD1G93A lumbar spinal cord before motor symptom onset, and are primarily caused by SOD1G93A expression and do not vary greatly as a function of disease course.